Changing redox conditions at cold seeps as revealed by authigenic carbonates from Alaminos Canyon, northern Gulf of Mexico - Birgel, D; Feng, D; Roberts, H H; Peckmann, J (Chemical Geology, 2011)
Anaerobic oxidation of methane in anoxic sediments at cold seeps often leads to formation of authigenic carbonates close to the seafloor along continental margins. Recent work, however, indicated that the redox conditions in sediments may vary to some degree during seepage activity. In order to shed new light on the extent of this variability, authigenic carbonates from Alaminos Canyon lease block 645 of the northern Gulf of Mexico have been characterized by means of inorganic and organic geochemistry. The carbonates were collected from seep deposits representing various seafloor morphologies, including extensive pavements, mounds, fractured carbonate slabs surrounded by dense bivalve shells, and vestimentiferan tubeworm colonies. The deposits almost entirely consist of aragonite. The $δ$18O values of aragonite vary from + 2.6 to + 5.8‰ V-PDB, suggesting precipitation in slight disequilibrium with the surrounding pore fluids. The $δ$13C values of aragonite between − 33.9 and − 20.4‰ V-PDB agree with variable amounts of carbonate derived from oxidation of thermogenic methane and crude oil. Methane was primarily oxidized in an anaerobic process as revealed by the presence of 13C-depleted molecular fossils of methane-oxidizing archaea ($δ$13C values as negative as − 118‰) and sulfate-reducing bacteria ($δ$13C values as negative as − 97‰), the syntrophic partners in the anaerobic oxidation of methane. The observed inventories of molecular fossils in the authigenic carbonates mirror those of known consortia of anaerobic methane oxidizing archaea (ANME) and sulfate-reducing bacteria, namely the ANME-2/Desulfosarcina/Desulfococcus (DSS) and ANME-3/Desulfobulbus (DBB) consortia. In contrast, the same carbonates exhibit shale-normalized rare earth elements patterns that all display real negative Ce anomalies (Ce/Ce*  In contrast, the same carbonates exhibit shale-normalized rare earth elements patterns that all display real negative Ce anomalies (Ce/Ce* 13C values of the biomarkers of aerobic methanotrophs are as negative as − 58‰ and are consequently less 13C-depleted than the molecular fossils of the prokaryotes performing anaerobic oxidation of methane, a pattern in accord with culture experiments. Overall, our results suggest that redox conditions at cold seeps are variable. This variability probably reflects changes in seepage flux. The combination of an inorganic and an organic geochemical approach used here is promising to better assess the variability and diversity of past fluid and gas expulsion at seeps.
Keywords: ROV Jason (Remotely Operated Vehicle)